Conservation laws by means of a new mixed method. (October 2017) - Ruggieri, M.; Speciale, M.P.
Abstract: In this paper, by using a mixed approach, recently introduced by the authors, some conservation laws of partial differential equations are derived. The method merges the Ibragimov's method and the one by Anco and Bluman. In particular, by applying this new mixed method, we determine all zero-th order conservation laws of Chaplygin and Shallow Water equations, as well as new conservation laws for a second order partial differential equation involving an arbitrary function.